The evaluation of forensic characteristics and the phylogenetic analysis of the Ong Be language-speaking population based on Y-STR. (November 2018) - Fan, Haoliang; Wang, Xiao; Chen, Haixiang; Long, Ren; Liang, Anwen; Li, Wenhui; Chen, Jianhua; Wang, Weihuan; Qu, Yihong; Song, Tao; Zhang, Peng; Deng, Jianqiang
Highlights: Haplotype diversity and discrimination capacity were increased with the number of analyzed loci increased in present study. Conducting the research combining population genetic analyses with geographical and linguistic record of Lingao population. Put forward one conclusion that it's unconscionable that Lingao people are classified into Han Chinese absolutely from the perspective of linguistics and genetics. Abstract: The Ong Be language, an important branch of the Tai-Kadai language family, is one of the most distinctive languages on Hainan Island. Ong Be language speakers, who have lived in the Lingao district of Hainan Island for generations, were classified as Han Chinese in the early days of the establishment of the People's Republic of China but have distinct differences from the Han Chinese in language, lifestyle, customs and values and particularly in appearances and features. Currently, Y-chromosomal short tandem repeat (STR) haplotypes have been widely used in genetic applications, such as human forensics, historical investigations and genealogical research. In this study, 487 unrelated male individuals residing in the Lingao district volunteered, and their Y-STR haplotypes were investigated using the Yfiler and Yfiler Plus with 17 and 27 Y-STR loci, respectively. Furthermore, we combined our population data on the Lingao people with existing datasets from Asian nations (East, South and Southeast Asia) to explore the genetic variance and relationships with Han Chinese from different administrative regions in Northern and Southern China and Chinese ethnic minorities officially recognized by the PRC. Population comparisons demonstrated that the Lingao people had distant relationships with Asian nations at the national level and had relatively close genetic and linguistic relationships with Hainan Li and Guizhou Gelao, both of whom belong to the Tai-Kadai language family. The present results increase our understanding of the genetic relationships between the Lingao people and other groups, and further research in genetics and other areas is still needed to trace the origin of the Lingao people.